2017
DOI: 10.21608/jfds.2017.38911
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Whipped Cream as Affected by Addition of Β-Lactoglobulin and Α-Lactalbumin

Abstract: Effect of adding whey protein concentrate (WPC), β-Lactoglobulin (β-LG) and alfalactalbumin (α-LA) on the functional properties of Whipped cream was examined. Obtained results showed unchangeable values of pH, the highest pH was found when skim milk powder was used compared with other treatments. Higher overrun (%) was also found when β-Lactoglobulin (β-LG) and alfalactalbumin (α-LA) were incorporated in whipped cream than whey protein concentrate (WPC). Samples showed changeable values of whipping time .The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The results showed that whipped cream samples had cohesiveness values ranging from 0.47 to 0.53 for which the greatest value was found for whipped cream prepared with carrageenan and cremodan se 80 and the lowest value obtained was for whipped cream containing only κ‐carrageenan. El‐Abd et al (2017) investigated the impact of WPC on the functional qualities of whipped cream. They found that the inclusion of whey proteins enhanced the hardness and cohesiveness of whipped cream samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that whipped cream samples had cohesiveness values ranging from 0.47 to 0.53 for which the greatest value was found for whipped cream prepared with carrageenan and cremodan se 80 and the lowest value obtained was for whipped cream containing only κ‐carrageenan. El‐Abd et al (2017) investigated the impact of WPC on the functional qualities of whipped cream. They found that the inclusion of whey proteins enhanced the hardness and cohesiveness of whipped cream samples.…”
Section: Resultsmentioning
confidence: 99%
“…Gafour Walid & Esmat ( 2020) studied using hydrocolloids as a stabilizer blend in whipped cream. The results showed that whipped cream samples had cohesiveness values ranging from 0.47 to 0.53 for which the greatest value was found for whipped cream prepared with carrageenan and cremodan se 80 and the lowest value obtained was for whipped cream containing only κ-carrageenan El-Abd et al (2017). investigated the impact of WPC on the functional qualities of whipped cream.…”
mentioning
confidence: 99%